Sleeping arrangements - Wickham, Madeleine, 1969- (New York : St. Martin's Griffin, 2008)
Chloe, tired of her job making wedding dresses accepts an offer from a wealthy friend to bring her family to a villa in Spain for a week, but when they arrive they find the villa has been double booked, and the other occupant is a man that Chloe has a history with.
"Thomas Dunne books."
Library Journal, June 2008
Publisher's Weekly, February 2008
Booklist, May 2008
Adult
Adult
Keywords: Dysfunctional families -- Fiction; Vacations -- Spain -- Fiction; British -- Spain -- Fiction; Family life -- Fiction; Vacations -- Spain -- Fiction; British -- Fiction; Chick lit